Industrial Location At the Intra-Metropolitan Level: A Negative Binomial Approach - Josep Maria Arauzo-Carod; Elisabet Viladecans-Marsal (European Regional Science Association (ERSA), 2006)
The objective of this paper is to analyse the incidence of agglomeration economies on the new firms' location decisions inside metropolitan areas. Following the literature we consider that agglomeration economies are related to the concentration of an industry (location economies) and/or the size of the city itself (urbanisation economies). We assume that those economies differ according the technological level of firms. So we use a sample of new firms belonging to high, intermediate and low technology levels. Our results confirm those sectoral differences and show some interesting location patterns of manufacturing firms Taking into account the renovated debate about the importance of the geography and distance in the location of economic activity, we introduce in the estimation the effect of the central city size as determinant for the location of new firms in the rest of the metropolitan area. This allows us to analyse if a suburbanisation effect exists and if that effect is the same depending on the industry and the central city size of the metropolitan area. Our main statistical source is the REI (Spanish Industrial Establishments Register), which has plant-level microdata for the creation and location of new industrial firms.
Keywords: 330